Annexin A2 promotes angiogenesis after ischemic stroke via annexin A2 receptor – AKT/ERK pathways. (1st January 2023) - Lin, Haoran; Li, Wenlu; Shen, Zexu; Bei, Yun; Wei, Taofeng; Yu, Zhanyang; Dai, Yunjian; Dai, Haibin
Highlights: Annexin A2 (ANXA2) attenuated OGD injury and improved behavioral recovery after focal cerebral ischemia. ANXA2 increased tube-formation and migration of brain endothelial cells either under normal condition or after OGD injury and promoted angiogenesis after focal cerebral ischemia. ANXA2 interacted with ANXA2 receptor to activate AKT/ERK pathways and then increased tube-formation and migration of brain endothelial cells after OGD injury. Abstract: Promoting angiogenesis to restore circulation to the ischemic tissue is still an important therapeutic target in stroke. Our group and others previously reported that the Ca 2+ -regulated, phospholipid-and membrane-binding protein-Annexin A2 (ANXA2) functions in cerebrovascular integrity and retinal neoangiogenesis. Here, we hypothesized that ANXA2 may regulate angiogenesis after stroke, ultimately improve neurological outcomes. Compared with wild type (WT) mice, the density of microvessels in brain and the number of new vessels sprouting from aortic ring were significantly increased in Anxa2 knock-in ( Anxa2 KI) mice. After focal cerebral ischemia, proliferation of brain endothelial cells in Anxa2 KI mice was significantly elevated at 7 days post-stroke, which further improved behavioral recovery. To assess the pro-angiogenic mechanisms of ANXA2, we used brain endothelial cells cultures to investigate its effects on cell tube-numbers and migration. Recombinant ANXA2 increased tube-numbers and migration of brain endothelial cells either under normal condition or after oxygen glucose deprivation (OGD) injury. Co-immunoprecipitation experiments demonstrated that these protective effects of recombinant ANXA2 were regulated by interaction with ANXA2 receptor (A2R), a protein found in cancer cells that can interact with ANXA2 to promote cell migration and proliferation, and the ability of ANXA2-A2R to activate AKT/ERK pathways. Inhibition of AKT/ERK diminished recombinant ANXA2-induced angiogenesis in vitro. Taken together, our study indicates that ANXA2 might be involved in angiogenesis after ischemic stroke. Further investigation of ANXA2-A2R will provide a new therapeutic target for stroke.